Analisis Kualitas Pengungkapan Laporan Keuangan Dalam Website Pemerintah Daerah - Septem Al Asyari; Herlina Helmy (Universitas Negeri Padang, 2020)
The research aims to determine the extent of the quality of local government websites in regencies / cities in Bengkulu and the provision of website services that are transparent, accountable, and accessibility. The research approach used is quantitative-descriptive. Documentation, literature, and interviews are used in the process of collecting data using scoring analysis techniques. The results of this research showed: (1) the quality of local government websites in districts / cities in Bengkulu is still low (2) the low causative factor of local government websites is the limited information on the website especially financial information and the lack of evaluation conducted by the government (3) steps that can be taken in order to overcome these obstacles, namely regular training of human resources in the management of local government website, evaluation of website development, and application of sanctions on local government websites that are not in accordance with standards.